Analisis Strategi Pengembangan Desa Wisata Halal Berbasis Kearifan Lokal di Nagari Maek Kecamatan Bukik Barisan - Kersy Novia (UIN Mahmud Yunus Batusangkar, 2023)
Community empowerment through tourism is by developing the potential of local resources through tourism villages. The development of halal tourism villages in West Sumatra is becoming a trend, Nagari Maek develops existing tourism potential by offering local wisdom from the regional community itself. The purpose of this study is to see how the development strategy for Halal Tourism Villages Based on Local Wisdom in Nagari Maek, Bukik Barisan District. This research uses qualitative research methods with a descriptive approach conducted with in-depth interviews and direct observation in the field. Based on the results of research conducted by the halal tourism village development strategy based on local wisdom in Nagari Maek, it promotes, seeks and collaborates with investors and cooperates with the government in the procurement of attractions, accessibility, amenity, and anciliary. The form of application of halal tourism villages based on local wisdom is to get the community as the main actors in a tourist attraction by prioritizing sharia values.